A case of recurrent lipoma in the sole with long-term follow-up. (June 2016) - Yasumura, Kazunori; Satake, Toshihiko; Shibuya, Mai; Ogawa, Marina; Kobayashi, Shinji; Mikami, Taro; Maegawa, Jiro
Abstract: We report a rare lipoma in the sole detected at 18 months of age. The lipoma recurred repeatedly and he underwent a third excision at 10 years of age. Although recurrence was clear at 18 years of age, no growth has been observed over the last 8 years.